STUDY OF SLA PRINTING PARAMETERS AFFECTING THE DIMENSIONAL ACCURACY OF THE PATTERN AND CASTING IN RAPID INVESTMENT CASTING - Badanova, Nazym; Perveen, Asma; Talamona, Didier (Journal of Manufacturing and Materials Processing, 2022)
Dimensional accuracy and geometric characteristics of the manufactured parts bear significant importance in product assembly. In Rapid Investment Casting, these characteristics can be affected by the printing parameters of the Additive Manufacturing method used in the pattern production process. Stereolithography is one of the important AM techniques mostly exploited in RIC due to its accuracy, smooth surface, and precision. However, the effect of SLA printing parameters on the dimensional accuracy and geometric characteristics have not been studied thoroughly. This study considers an experimental approach to study the effect of SLA printing parameters such as layer thickness, build angle, support structure density, and support touchpoint size on the dimensional accuracy and geometrical characteristics of the Castable Wax printed patterns and the Al cast parts. Taguchi’s Design of Experiment was used to define the number of experimental runs. SolidCast simulation was used to design the orientation of casting feeder to achieve directional solidification. Coordinate Measuring Machine measurements of deviations in the printed and cast parts were analyzed using the “Smaller-the-better” scheme in the two-step optimization method of Taguchi experiments. Build angle and Layer thickness were identified to be the first and the second most impactful parameters, respectively, affecting both the dimensional and geometric accuracy of Castable Wax patterns and Al cast parts, with optimal values of 0 deg and 0.25 μm, respectively. Both printed and cast parts had twice as many deviations in geometry as in dimensions. The sphere roundness and angularity were found to be the most and least accurate geometric characteristics, respectively. The dimensions in the Z direction were more accurate than in the X-Y directions, showing the smallest size deviations for height measurements and large deviations in the length, width, and diameter of the hole.
Keywords: Type of access: Open Access; rapid investment casting; stereolithography; additive manufacturing; dimensional accuracy